Evaluasi dan Uji Kualitas Website dengan Metode Webqual (Studi Kasus: STMIK Sumedang) - Muhammad Agreindra Helmiawan; Yopi Hidayatul Akbar; Yan Yan Sofian (LPPM STMIK AMIK BANDUNG, 2019)
Information and interaction in an information media is very important in delivering information to users. This information will be well received if there is continuous interaction, and it becomes an indicator of the quality of the information media. The research was conducted aimed at testing information media in the form of websites, especially the STMIK Sumedang website and evaluating the quality of the STMIK Sumedang web from user responses in the form of usability, information quality and interaction quality. This research uses WebQual 4.0 which is compiled based on three qualities, namely ease of use (usability), information quality (information quality) and quality of interaction (interaction quality). The results of this study are that the STMIK website is good enough but there are still procedures in the web menu that are not working. From this study it can be concluded the most influential in the quality of the web is the usability variable can be seen from the following results Y = - 7.174 + 0.479 X1 + 0.182 X2 + 0.060 X3, X1 = usabiliti, X2 = quality of information, X3 = quality of interaction.